Utilization of wheat germ oil and wheat bran fiber as fat replacer for the development of low‐fat beef patties. Issue 3 (22nd January 2021) - Khalid, Anam; Sohaib, Muhammad; Nadeem, Muhammad Tahir; Saeed, Farhan; Imran, Ali; Imran, Muhammad; Afzal, Muhammad Inam; Ramzan, Sana; Nadeem, Muhammad; Anjum, Faqir Muhammad; Arshad, Muhammad Sajid
Abstract: The present study was aimed to evaluate the effects of wheat germ oil and wheat bran fiber as fat replacers on quality and stability of low‐fat beef patties. Total five treatments were prepared by employing wheat germ oil (WGO) and wheat bran fiber (WBF). WBF was used at fixed amount of 3% in all treatments except control in conjunction with varying WGO concentrations as follows: 1.5%, 3%, and 4.5%. Prepared raw and cooked beef patties were stored at 4°C, and further analyses were carried out up to 21 days of storage period with intermittent evaluation interval of 7 days. Higher values of TBARS, peroxide, and cholesterol were observed in raw and cooked beef patties in control, whereas minimum values were found in treatment of beef patties prepared with WGO 4.5% + WBF 3%. The physicochemical parameters were observed by pH and hunter color values. pH was higher in cooked patties as compared to beef patties and showed increases with increase in WGO concentration and storage intervals. The sensorial attributes were observed which included different parameters, such as appearance, texture, taste, odor, and overall acceptability. Higher score was given by the panelists to control for both raw and cooked beef patties; however, minimum score for all sensory properties was found in group treated with WGO 4.5% + WBF 3% within acceptable limit. In nutshell, raw and cooked beef patties treated with WGO 4.5% plus WBF 3% showed better quality, stability, and reduced cholesterol content. Abstract : In nutshell, raw and cooked beef patties treated with wheat germ oil 4.5% plus wheat bran fiber 3% showed better quality, stability, and reduced cholesterol content.